2003
DOI: 10.1089/107999003321829953
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators and Skeletal Muscle Injury: A DNA Microarray Analysis

Abstract: Traumatic skeletal muscle injury causes a specific sequence of cellular events consisting of degeneration, inflammation, regeneration, and fibrosis. The role of early posttraumatic mechanisms, including acute inflammatory response, in muscle repair is not well understood. In the present study, oligonucleotide microarray analyses were used to examine the candidate genes that are involved in these early events of the muscle injury/repair process. cDNA was prepared from the injured and control tibialis anterior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 25 publications
1
43
2
1
Order By: Relevance
“…The results of eight previously published regeneration-related genomic analyses were selected for comparison to the microarray results (Ishino et al, 2003;King et al, 2003;Summan et al, 2003;Katogi et al, 2004;Swamy et al, 2004;Wolfe et al, 2004;Reddien et al, 2005;Schnapp et al, 2005;Tazaki et al, 2005). Due to the variety of organisms studied in these articles and the information provided, different approaches were taken to compare them to the Xenopus data.…”
Section: Comparisons To Previously Published Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of eight previously published regeneration-related genomic analyses were selected for comparison to the microarray results (Ishino et al, 2003;King et al, 2003;Summan et al, 2003;Katogi et al, 2004;Swamy et al, 2004;Wolfe et al, 2004;Reddien et al, 2005;Schnapp et al, 2005;Tazaki et al, 2005). Due to the variety of organisms studied in these articles and the information provided, different approaches were taken to compare them to the Xenopus data.…”
Section: Comparisons To Previously Published Resultsmentioning
confidence: 99%
“…Putative human orthologs are provided as available. The "Notes" column indicates the following: identified as up-regulated in Xenopus tail regeneration in Tazaki et al (2005); identified as down-regulated in Xenopus tail regeneration in Tazaki et al (2005); found differentially expressed in st53/ st59 Xenopus laevis hindlimbs in King et al (2003); and found to be up-regulated in skeletal myogenesis by Summan et al (2003).…”
Section: The Most Statistically Significant Hits From Comparisons a mentioning
confidence: 99%
See 2 more Smart Citations
“…40,41 We suggest that the different characteristics of SASCs from noninjured muscle and injured muscle are related to their modified expression of certain functional genes. Using semiquantitative RT-PCR, we analyzed the expression of several genes related to stem cell multipotency, muscle development, and muscle regeneration to determine whether SASCs from noninjured muscle may express these genes and whether muscle injury may modify expression of these genes in SASCs.…”
Section: Some Genes Related To Muscle Development or Stem Cell Regulamentioning
confidence: 97%